Pengaruh Kepribadian, Gaya Hidup dan Konsep Diri Terhadap Keputusan Pembelian Produk Kecantikan Ms Glow Pada Masyarakat Tembung Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Sambas, Rizky Aulia; Siregar, Muhammad Yamin; Tarigan, Eka Dewi Setia (Economics, Business and Management Science Journal, 2025)
This study aims to test "the influence of personality, lifestyle and self-concept on the purchase decision of ms glow beauty products on the people of Tembung, Percut Sei Tuan District, Deli Serdang Regency". This type of research is associative, which is research with the aim of finding out the relationship of influence between two or more variables. The population in this study is the entire community of Tembung, Percut Sei Tuan District, Deli Serdang Regency who use ms glow beauty products, whose number is not known for sure. The sampling method uses Leme show. The number of samples used in this study was 96 people. The data analysis in this study included a validity test, reliability test, normality test, a multicollinearity test, a heteroscedasticity test, multiple linear regression analysis, t-test, f-test, and determinant coefficient test (r2) using the statistical package for the social science for Windows (spss) 25. Based on the r2 test, a value of 0.162 was found. This states that the variables of personality, lifestyle, and self-concept affect the purchase decision by 16.2%, while the remaining 83.8% are influenced by variables that are not studied in this study.